Pulmonary aspergillosis: diagnosis and treatment. (30th November 2022) - Lamoth, Frederic; Calandra, Thierry
Aspergillus species are the most frequent cause of fungal infections of the lungs with a broad spectrum of clinical presentations including invasive pulmonary aspergillosis (IPA) and chronic pulmonary aspergillosis (CPA). IPA affects immunocompromised populations, which are increasing in number and diversity with the advent of novel anti-cancer therapies. Moreover, IPA has emerged as a complication of severe influenza and coronavirus disease 2019 in apparently immunocompetent hosts. CPA mainly affects patients with pre-existing lung lesions and is recognised increasingly frequently among patients with long-term survival following cure of tuberculosis or lung cancer. The diagnosis of pulmonary aspergillosis is complex as it relies on the presence of clinical, radiological and microbiological criteria, which differ according to the type of pulmonary aspergillosis (IPA or CPA) and the type of patient population. The management of pulmonary aspergillosis is complicated by the limited number of treatment options, drug interactions, adverse events and the emergence of antifungal resistance. The clinical spectrum of pulmonary aspergillosis has broadened with the recognition of novel patient populations at risk and the emergence of resistance, which poses important diagnostic and therapeutic challenges for clinicians https://bit.ly/3R6Cf6Z